Antitumor and hepatoprotective effect of Cuscuta reflexa Roxb. in a murine model of colon cancer. (10th January 2022) - Mishra, Shobhit; Alhodieb, Fahad Saad; Barkat, Md. Abul; Hassan, Mohd. Zaheen; Barkat, Harshita Abul; Ali, Raisuddin; Alam, Perwaiz; Alam, Ozair
Abstract: Ethnopharmacological relevance: Cuscuta reflexa Roxb. ( C. reflexa ) is a well-known traditional herbal plant, with numerous inherent therapeutic potentials including anticancer, antitumor, antibacterial, analgesic, anthelmintic, laxative and others. Moreover, the anticancer and antitumor potentials of this herb are ongoing with several trails, thus an attempt was made to assess the anticancer and hepatoprotective potentials of traditional C. reflexa herbs. Method: The dried ethanolic extract of C. reflexa was tested for acute oral toxicity in the treated animals subsequently their behavioral, neurological, and autonomic profiles changes were observed. T he preliminary anti-cancer effects of extracts against 1, 2- Dimethyl hydrazine (DMH) induced animals were assessed through barium enema X-ray, colonoscopy, and Aberrant crypt foci (ACF) studies. The blood samples of the animals (treated and untreated) were collected and their in-vitro histological parameters were evaluated by the experienced technician. Results: It was observed that C. reflexa significantly reduced Disease activity indexing (DAI) level and ACF counting, as well as demonstrated similar activity as of the standard drug 5-Fluorouracil (5-FU). Histopathological results revealed that the apoptotic bodies decreased in the DMH-induced group (group II) during cancer progression while in 5-FU treated (group III) and C. reflexa treated (group IV and V) animals the apoptotic bodies were increased. Inversely, the mitotic bodies increased in group II animals and reduced in group III, IV, and V animals. In the colonic section, DMH-induced cancer assay exhibited significant effects on the levels of hemoglobin, Packed cell volume (PCV), Red blood cell (RBC) counts, Mean corpuscular hemoglobin concentration (MCHC), Mean corpuscular volume (MCV), and Mean cell hemoglobin (MCH), and was found to be less in group II animals whereas administration of C. reflexa efficiently recovered back the loss probably by healing the colon damage/depletion of cancer progression. Moreover, compared to the group II animals, the neutrophil count was within the normal range in C. reflexa administered group. Conclusions: In the present study, the major hematological parameters significantly increased within DMH treated animals and exhibited extensive damage in the hepatic regions. Moreover, the histopathological findings demonstrated that the C. reflexa extracts potentially reduced the cell proliferation, with no toxicity. The C. reflexa extracts exhibited impending anti-cancer activity as well as protected the hepatic cells and thus could be potentially used in the management of colon or colorectal cancer and hepatic impairments. Graphical abstract: Image 1 Highlights: Cuscuta Reflexa Roxb. treated animals showed improved results in hepato-specified factors . Histopathological parameters were significantly improved in C. reflexa treated animals. Animals given C. reflexa showed a probable reduction in tumor progression, which signifies its anti-colon cancer activity. C. reflexa treated animals exhibited negligible toxicity in the hepatic environment.